2012
DOI: 10.1088/0960-1317/22/9/095001
|View full text |Cite
|
Sign up to set email alerts
|

Continuous particle focusing in a waved microchannel using negative dc dielectrophoresis

Abstract: We present a waved microchannel for continuous focusing of microparticles and cells using negative direct current (dc) dielectrophoresis. The waved channel is composed of consecutive s-shaped curved channels in series to generate an electric field gradient required for the dielectrophoretic effect. When particles move electrokinetically through the channel, the experienced negative dielectrophoretic forces alternate directions within two adjacent semicircular microchannels, leading to a focused continuous-flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 45 publications
4
53
0
Order By: Relevance
“…It could be found that applied voltages at both inlet and outlet could affect particle trajectory, and 15 μm particles can be directed into either outlet 1 or outlet 2 depending on the applied voltages. In addition, with the increase of inlet and/or outlet voltage, 15 μm particles were observed to obtain a better focusing effect (forced into a narrower stream), which corresponds to our pervious founding [12]. By setting the correction factor to be 0.4 for 15 μm particles, the numerically predicted results (right column) coincide acceptably with the experimentally obtained superimposed images.…”
Section: Numerical Simulationsupporting
confidence: 84%
See 1 more Smart Citation
“…It could be found that applied voltages at both inlet and outlet could affect particle trajectory, and 15 μm particles can be directed into either outlet 1 or outlet 2 depending on the applied voltages. In addition, with the increase of inlet and/or outlet voltage, 15 μm particles were observed to obtain a better focusing effect (forced into a narrower stream), which corresponds to our pervious founding [12]. By setting the correction factor to be 0.4 for 15 μm particles, the numerically predicted results (right column) coincide acceptably with the experimentally obtained superimposed images.…”
Section: Numerical Simulationsupporting
confidence: 84%
“…Consider a particle subjected to negative DEP effect passing though the microchannel under the combined effect of EOF and EP, repulsive DEP forces (dark blue arrows, relatively weak in the curved section, while strong in the constricted region) are exerted on the particle all along its movement. The detailed fabrication process of the polydimethylsiloxane (PDMS)-based microfluidic device can be found in our previous work [12]. As shown in Fig.…”
Section: Theory and Mechanismmentioning
confidence: 99%
“…Various manipulation techniques have already been proposed and developed to focus particles in microfluidics, such as dielectrophoresis [4][5], magnetophoresis [6][7] and acoustophoresis [8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Consider a particle subjected to negative DEP effect passing though the microchannel under the combined effect of EOF and EP, repulsive DEP forces (dark blue arrows, relatively weak in the curved section, while strong in the constricted region) are exerted on the particle all along its movement. The polydimethylsiloxane (PDMS) microfluidic channel was fabricated using standard soft-lithography technique, and a detailed fabrication process can be found in our previous work [15]. As shown in Figure (2), the microfluidic chip is composed of two semi-circular channels that each integrates with three round hurdles from inner wall, one inlet (A) and two outlet (B and C) reservoirs, and three straight connecting microchannels.…”
Section: Theorymentioning
confidence: 99%